(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article explores how interactive story-based writing tasks enhance creativity and text organization skills among primary EFL learners. Drawing on classroom observations, qualitative analysis, and digital storytelling activities, the study demonstrates that story-based tasks significantly motivate young learners, support coherent narrative construction, and encourage imaginative thinking. Digital tools—such as StoryJumper, Book Creator, and online story generators—provide visual scaffolds that help students plan events, develop characters, and sequence ideas logically.